Analisa Alat Ukur Tinggi Badan Berbasis Internet of Things Menggunakan Sensor Ultrasonic: Teknik Elektronika - Gunawan, Dike Musta; Lutfi, Iskandar; Damsi, Faisal (Teknik Elektro Polsri, 2023)
Height measuring device is a tool used to measure a person's height. The commonly used height scale is the manual type which reads the measured height. Manual measurement in today's modern era is very ineffective when used on a large scale, especially in this era where there are so many digital tools. The specialty of this automatic height measuring device is that it can easily measure the height of many people. The operating system of this tool is to measure height automatically, so that measurement data can be stored automatically in the database. Compared to analog measuring devices that only measure one object and cannot store measurement data. In this study the authors made an automatic height measuring tool different from the usual. The author developed a previous automatic height measuring device using two ultrasonic sensors. The first ultrasonic sensor is used as a height meter and the second ultrasonic sensor is installed at the bottom to detect the legs to avoid cheating and also adds a measuring mat above the head so that the height measurement is really accurate. Key words : Height Measurement, Internet of Things, Ultrasonic Sensors